Preterm meconium-stained amniotic fluid is an ominous sign for the development of chorioamnionitis and for in utero cord compression. (2nd September 2017) - Brabbing-Goldstein, Dana; Nir, Dan; Cohen, Deborah; Many, Ariel; Maslovitz, Sharon
Abstract: Purpose: Meconium-stained amniotic fluid (MSAF) is rarely observed in preterm pregnancies, and its clinical significance is undetermined. We evaluated the correlation between MSAF and obstetrical and perinatal complications prior to 34 weeks' gestation. Materials and methods: Pregnancies complicated with MSAF between 24 and 34 weeks of gestation were compared with same gestational age-matched controls. The variables measured were: obstetrical complications: clinical chorioamnionitis, Intrahepatic Cohlestasis of Pregnancy – ICP, Intra Uterine Growth Restriction – IUGR, preeclampsia, gestational diabetes; nonobstetrical complications; and perinatal complications: cord around neck/body, Apgar <7 at 5 min, cord pH, Neonatal Intensive Care Unit – NICU admission, complications during NICU hospitalization, and composite outcome. Results: Higher incidence of clinical chorioamnionitis (15% versus 4.3%; p = 0.041) and higher incidence of cord around the neck/body were found in the MSAF group in comparison with the clear AF group (27.4% versus 18.4%; p = 0.04). No significant differences between the study's groups were found in nonobstetrical complications or other perinatal complications investigated in our study. Conclusion: MSAF in preterm pregnancy is an ominous sign for the occurrence of chorioamnionitis and for in utero cord compression. Therefore, MSAF in preterm pregnancies should be considered as a non-reassuring sign.